Potensi peningkatan hasil kacang tanah (Arachis hypogaea L.) melalui kombinasi aplikasi NPK dan pupuk guano - Amir, Nurbaiti; Palmasari, Berliana; Syafrullah, Syafrullah; Irawan, Eka Ari (Universitas Muhammadiyah Mataram, 2022)
This study aims to determine and determine the dose of NPK fertilizer with the appropriate application of guano fertilizer on the yield of peanuts (Arachishypogaea L.), The study was conducted from September to December 2020, this study used a split plot design with 3 replicates for a total of 27 plots. The treatment variables were NPK fertilizer (N), namely N1 = 25 kg ha-1; N2 = 50 kg ha-1 ; N3 = 75 kg ha-1 and Guano Fertilizer (G) ie G1 = 5 tons ha-1; G2 = 10 tons ha-1 ; G3 = 15 tonnes ha-1. Observational variables in this study included the number of pods per plant (pods), pod weight per plant (g), weight of 100 seeds (g) and weight of pods per plot (kg). The results showed that combination of NPK fertilizer 75 kg ha-1 with guano fertilizer 10 tons ha-1 gave the highest yield of peanuts at 1.49 kg per plot (2.98 tons ha-1).